Implementasi Program KUA Goes to School Tentang Pendewasaan Usia Pekawinan dalam Upaya Pencegahan Pernikahan Dini Perspektif Maqashidasy- As’yariah - Yuli Widiyawati; Ishaq; Sri Lumatus Sa'adah (Jurnal Syntax Admiration, 2023)
This research aims to analyze the implementation of the "KUA Goes To School" program related to marriage age maturity as an effort to prevent early marriage at the Office of Religious Affairs (KUA) in Silo District, Jember Regency, considering the perspective of Maqashidasy-As’yariah. This study utilizes a qualitative method with a case study approach. The results of the research indicate that the "KUA Goes To School" program has significantly contributed to raising awareness among the community, especially students, regarding the importance of marriage age maturity. Based on the Maqashidasy-As’yariah analysis, the implementation of this program has successfully protected specific individual rights, safeguarded the general rights of the community, and promoted social welfare. However, there are some challenges that need to be addressed in the implementation of this program, such as the lack of active involvement from certain relevant parties and insufficient resources. Therefore, it is recommended to enhance collaboration among stakeholders and allocate resources more efficiently. This research provides valuable insights into the implementation of the "KUA Goes To School" program in the context of preventing early marriage in Jember Regency, considering the aspects of Maqashidasy-As’yariah. The results of this research are expected to make a valuable contribution to efforts to prevent early marriage in similar regions and provide a foundation for the improvement and development of similar programs in the future.